A review of Apis mellifera caucasica (Hym., Apidae): History, taxonomy and distribution - Irakli Janashia; Layne Westover; George Japoshvili (Journal of Insect Biodiversity and Systematics)
The taxonomic status and placement of the Caucasian honey bee (Apis mellifera caucasica Gorbachev, 1916) (Hymenoptera: Apidae) remains puzzling, largely based on outdated investigations. After reviewing available scientific sources, we conclude that initially there was a confusing mismatch between the traditional geographical understanding of the Caucasus and the actual distribution of A. m. caucasica. Insufficient geographic sampling of honeybees across the Caucasus, a statistically inadequate number of studied samples, and incomplete research methodology are major drawbacks of previous studies. Morphometric reference data derived from an extremely limited number of samples still is in use as a standard for the identification of A. m. caucasica. It is highly probable, that this standard does not reflect true morphometric diversity, covering natural geographical variations, which most importantly hinder preservation or breeding efforts. To resolve these deficits, honeybees of the Caucasus and adjacent regions need to be studied in more detail with greater depth of sampling. A thorough study, using modern morphometric approaches and molecular genetic methods, is needed to characterize A. m. caucasica and produce a statistically robust dataset for due reconsideration of its taxonomic status and placement.